Numerical Simulation and Experimental Study of Shot Peening on Rough Surface based on FEM-DEM - Mingming Deng; Guixi Peng; Ming Zheng; Changjiang Zhou (Jixie chuandong)
A finite element and discrete element （FEM-DEM） coupling model for shot peening on rough surface is proposed in consideration of the surface roughness of non-peened specimen. The peened and non-peened 45# steel specimens are prepared，and their residual stress on the surface and subsurface are measured. The measured results are used to verify the proposed model，and the effects of shot peening process parameters on the residual stress on the subsurface are studied. The results show that increasing the surface coverage and shot peening intensity can increase the peak value of the compressive residual stress，especially the impact of shot peening is more significant. With the same surface coverage and shot peening intensity，the smaller diameter shot can increase the peak value of the compressive residual stress，while the thickness of the compressive residual stress increases as the diameter of shot becomes larger. If the surface roughness before shot peening is too high，the effect of shot peening can be enhanced by increasing the surface coverage. The research provides a certain theoretical basis for the optimization of shot peening on the rough surface.